Association of Coral Life Form with Megabenthos, Pasumpahan Island, Padang City - Syukra, Rera Agung; Salihat, Rera Aga; Nuraini, Miranda (Jurnal Biologi Tropis, 2025)
Pasumpahan Island is a popular tourist destination in the Padang area. Increasing tourist activity is suspected to contribute to the degradation of the coral reef ecosystem, as observed during preliminary surveys. Coral reef degradation can significantly impact associated marine organisms, particularly megabenthos species. This study examined the association between coral life forms and megabenthos types through direct field observations. A quadrat method was applied using 5×5 m² plots across nine locations. Data analysis employed 2x2 contingency tables, and association strength was quantified using the Ochiai Index. Researchers identified six coral life forms and four megabenthos types, producing 45 potential association combinations. Results indicated that 39 combinations exhibited no association. The remaining six showed associations, equally divided between positive and negative. Positive associations occurred between mushroom corals and Acanthaster planci, massive corals and Tridacna spp., and encrusting corals and Trochus spp. These relationships were identified as commensal, where species coexist without direct harm. Negative associations were found between massive and encrusting corals, encrusting corals and Tridacna spp., and encrusting corals and Diadema setosum. The Ochiai Index proved effective in detecting species interactions and supporting coral reef ecosystem assessments.